Nanocomposite paste for bone repair - Abu Bakar @ Zakaria, Md Zuki; Islam, Kh. Nurul; Mohamad Yusof, Loqman (2013)
The present invention relates to nanocomposite bone paste for bone repair and to a method for preparation of nanocomposite of the present invention. The method for preparation of the nanocomposite for bone repair comprises the steps of; a) providing fine cockle shells powder; b) adding water and dodecyl dimethyl betaine (BS-12) while stirring forming a mixture; c) filtering the mixture to obtain nanoparticles of Calcium carbonate; d) drying the nanoparticles Calcium carbonate; e) adding chitosan solution to the nanoparticle Calcium carbonate while stirring forming nanocomposite paste; and f) irradiating the nanocomposite paste.